It feels good to be yourself : a book about gender identity - Thorn, Theresa (Henry Holt and Company, 2019)
A picture book that introduces the concept of gender identity to the youngest reader from writer Theresa Thorn and illustrator Noah Grigni. Some people are boys. Some people are girls. Some people are both, neither, or somewhere in between. This sweet, straightforward exploration of gender identity will give children a fuller understanding of themselves and others. With child-friendly language and vibrant art, It Feels Good to Be Yourself provides young readers and parents alike with the vocabulary to discuss this important topic with sensitivity.